Aplikasi Perhitungan Persediaan Bahan Baku dengan Metode Economic Order Quantity Berdasarkan Varian Produk - Rianti Rahmawati; Anak Agung Gde Agung; Fitri Sukmawati (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2016)
CV Dwi Sumber is one of manufacture company which handles sales with variant product. Recording process of raw materials from the warehouse until production process was done manually. The company ordered raw material with the same amount without checking the stock quantity available in the warehouse. For every order, the company must pay order fee. Transactions record were also done manually so it was not directly reduce the stock of raw materials in the warehouse. This accumulated to overstock in the warehouse. This application used Economic Order Quantity (EOQ) to calculate optimal raw material order so it can reduce order fee. This application can also record transaction, automatically reduce stock in the warehouse, calculate safety stock in the warehouse so management can decide when they have to reorder the raw material. Transaction record can be viewed as accounting journal and general ledger. This application is built using PHP programming language and MySQL database.